"I smile, but Without Showing My Teeth": The Lived Experience of Cleft, Lip, and Palate in Adults. (July 2020) - Moi, Asgjerd Litleré; Gjengedal, Harald; Lybak, Kari; Vindenes, Hallvard
Objective: To explore and describe the experience of growing up with unilateral cleft lip and palate (CLP) in adults. Design: Face-to-face interviews. Giorgi's phenomenological method was used for analysis. Participants: Twenty-one (mean age: 40.8 years) adults treated for unilateral CLP during childhood and adolescence participated in the study. Results: Growing up with CLP meant to become aware of bodily otherness. The possible reactions from peers early in life complicated the striving for inclusion outside the close family. Being self-confident, clever in school, physically fit, and having trusted friends represented barriers against teasing and bullying. Nevertheless, the reflected image, in mirrors, windows, and photos, reminded the participants of the objectifying looks from others and often led to bodily adjustments that persisted into adulthood. The trajectory of treatment was not questioned during childhood, and the participants accepted the decisions on care made by experts and parents. Although problems related to the cleft could persist or return after the termination of ordinary treatment, a more hesitant view on the possible benefits of additional surgery was typical in adulthood. Conclusions: In retrospect, growing up with a unilateral CLP was found to have been an unquestioned part of the adult participants' childhood, a burden that they feared would, to some extent, also be passed to their own children. However, the CLP had not prevented them from achieving goals and satisfaction in life. The occurrence of persisting psychological, functional, and esthetic challenges in adults suggests the need for an individualized, lifelong, and multidisciplinary perspective on CLP follow-up.